Food consumption and nutritional status: characterization of physically active women - Geisa Oliveira Rocha; Isabela Simões de Boucherville Pereira; João Paulo Lima de Oliveira; Wilson César de Abreu (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Few studies have characterized the food consumption and nutritional status of physically active women. The aim of this study was evaluating the food consumption and nutritional status of physically active women. Thirty women aged between 18 and 59 years, who trained at least three times a week, were evaluated. Weight, height, waist circumference (WC), and Body Mass Index (BMI) were checked. The percentage of body fat (%BF) was determined by the seven-skinfold protocol. Food consumption was assessed from the 72 food records collected on non-consecutive days. The records were analyzed using the DietPro 5i Program. The evaluated population had the following anthropometric characteristics: (Weight = 64.13 ± 10.16 kg, Height = 1.64 ± 0.06 m, BMI = 23.91 ± 3.04 kg/m2, WC = 77.48 ± 9.36 cm, %BF = 25.35 ± 4.65); 33% were overweight and 30% had elevated WC. BMI showed a strong and positive correlation with% WC (r=0.70, p<0.001) and with WC (r = 0.84, p<0.001). The average daily consumption of energy and nutrients were: (Energy = 24.5 ± 7.0 Kcal/kg/day, Carbohydrates = 3.1 ± 1.1 g/kg/day, Proteins = 1.1 ± 0.3 g/kg/day, Lipids = 0.9 ± 0.4 g/kg/day, Fiber = 16.7 ± 6.2 g/day, Calcium = 556.2 ± 165.3 mg/day and Iron = 9.8 ± 2.1 mg/day). Most women consumed inadequate energy, carbohydrates, proteins, fiber, and iron. No woman achieved the recommended minimum calcium intake. It is concluded that an expressive portion has BMI, WC and% BF above the desirable values ​​that are associated with healthy nutritional status. In addition, the significant percentage of inadequate consumption of energy, carbohydrates, proteins, fiber, calcium, and iron reveals the need for professional guidance.